2018
DOI: 10.1007/s00264-018-3992-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and patterns of meniscal tears accompanying the anterior cruciate ligament injury: possible local and generalized risk factors

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 39 publications
6
61
0
2
Order By: Relevance
“…statistically significant p values are bold with fields marked in gray have a higher rate of degenerative tears which is consistent with some previous studies [33]. However, other studies have reported a male predilection for meniscal tears due to traumatic lesions [34] and non-horizontal tears [35]. Our study results confirmed that the posterior horn is the most affected region for meniscal degeneration [13,18,19,36] and anterior horn is less often affected [19].…”
Section: Discussionsupporting
confidence: 92%
“…statistically significant p values are bold with fields marked in gray have a higher rate of degenerative tears which is consistent with some previous studies [33]. However, other studies have reported a male predilection for meniscal tears due to traumatic lesions [34] and non-horizontal tears [35]. Our study results confirmed that the posterior horn is the most affected region for meniscal degeneration [13,18,19,36] and anterior horn is less often affected [19].…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, time to surgery correlates with the incidence of concomitant meniscus injuries [25,29]. In particular, the incidence of medial meniscus (MM) tears seems to significantly 1 3 increase with delayed surgery [26,50]. Conversely, patients with medial or lateral meniscus instabilities have a significantly increased risk of ACL failure after reconstruction [32].…”
Section: Introductionmentioning
confidence: 99%
“…5 However, it was shown that even in patients with isolated ACL tears, meniscal injuries could occur due to knee instability and pivot. 6 This type of secondary meniscal damage in patients with long-standing ACL tear would contribute to knee later arthritic changes. 2,[7][8][9] Previous studies showed that patient's age, time from an ACL injury (TFI), sex, and obesity are predictors of meniscal tear in patients who underwent ACL reconstruction.…”
mentioning
confidence: 99%